GC×GC-TOFMS Analysis of Essential Oils Composition from Leaves, Twigs and Seeds of Cinnamomum camphora L. Presl and Their Insecticidal and Repellent Activities - Hao Jiang (Molecules, 2016)
Interest in essential oils with pesticidal activity against insects and pests is growing. In this study, essential oils from different parts (leaves, twigs and seeds) of Cinnamomum camphora L. Presl were investigated for their chemical composition, and insecticidal and repellent activities against the cotton aphid. The essential oils, obtained by hydrodistillation, were analyzed by GC×GC-TOFMS. A total of 96 components were identified in the essential oils and the main constituents found in the leaves and twigs were camphor, eucalyptol, linalool and 3,7-dimethyl-1,3,7-octatriene. The major components found in the seeds were eucalyptol (20.90%), methyleugenol (19.98%), linalool (14.66%) and camphor (5.5%). In the contact toxicity assay, the three essential oils of leaves, twigs and seeds exhibited a strong insecticidal activity against cotton aphids with LC50 values of 245.79, 274.99 and 146.78 mg/L (after 48 h of treatment), respectively. In the repellent assay, the highest repellent rate (89.86%) was found in the seed essential oil at the concentration of 20 μL/mL after 24 h of treatment. Linalool was found to be a significant contributor to the insecticidal and repellent activities. The results indicate that the essential oils of C. camphora might have the potential to be developed into a natural insecticide or repellent for controlling cotton aphids.